2009
DOI: 10.17221/79/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Teratoma adultum in a bitch: a case report

Abstract: This case report concerns a two year old female mongrel weighing about 25 kg which was admitted to an animal shelter. A grapefruit-sized mass was found in the animal’s left ovary during a routinely performed ovariohysterectomy. On sectioning, the mass revealed cysts containing tufts of hair in creamy white sebaceous fluid. A histological examination revealed a mixture of tissues. The tumor was diagnosed as a mature teratoma (teratoma adultum).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
(17 reference statements)
1
3
0
2
Order By: Relevance
“…Regarding age, according to the literature, these tumours occur more frequently in young animals [4,5,[7][8][9][10][11]. Similar situation was found in the present study, since it is a female dog two years and nine months old.…”
Section: Resultssupporting
confidence: 88%
“…Regarding age, according to the literature, these tumours occur more frequently in young animals [4,5,[7][8][9][10][11]. Similar situation was found in the present study, since it is a female dog two years and nine months old.…”
Section: Resultssupporting
confidence: 88%
“…However, they reiterate that there is still no scientific evidence to provide perspectives on gestation rates and number of puppies expected by adopting this type of management. Ovariohysterectomy has been recommended by several authors (1,3,6,8,10) and it was the treatment of choice in this case due to the secondary occurrence of pyometra. Added to this is the fact that, although there are clinical treatments available for pyometra, which, in theory, would allow the maintenance of the uterus and contralateral ovary, ovariohysterectomy is still the safest and most effective treatment for pyometra (13,18), in addition to the lack of reproductive interest on the part of the tutors.…”
Section: Discussionmentioning
confidence: 87%
“…Ovarian teratomas in female-canine are commonly benign (3,6,(8)(9)(10)16). According to Blaszak et al (3) and Brum et al (6), malignant metastases can be observed in the abdominal organs, lymph nodes, lungs and bones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations